A Multilevel Model of Compassion in Healthcare Organizations - Mabel San Román-Niaves; Marco De Angelis; Susana Llorens; Marisa Salanova (Journal of Work and Organizational Psychology)

(untitled)
This study investigates compassion’s role in healthcare, examining its relationship between job demands, job social resources, and well-being outcomes (engagement and burnout) across organizational levels. Data from 714 healthcare professionals in 35 Spanish hospital teams were collected using the Brief Compassion Scale and HERO questionnaire. Hierarchical linear modeling showed team-level job social resources positively associated with individual-level compassion (β = .65, p< .01). Compassion positively associated with engagement (β = .88, p< .001) and negatively with burnout (β = -.89, p< .001). Individual-level job demands negatively affected compassion (β = -.60, p< .001). These findings highlight compassion's role in improving engagement and mitigating burnout across organizational levels. The results emphasize the importance of fostering compassion and enhancing team job social resources to improve healthcare professionals’ well-being, offering valuable insights for understanding workforce dynamics in healthcare organizations.